2020
DOI: 10.1186/s12890-020-1169-z
|View full text |Cite
|
Sign up to set email alerts
|

Baseline low ALT activity is associated with increased long-term mortality after COPD exacerbations

Abstract: Background: COPD exacerbations have negative impact on patients' survival. Several risk factors for grave outcomes of such exacerbations have been descried. Muscle dysfunction and mass loss were shown to impact negatively on prognosis and survival. Low activity of the enzyme ALT (Alanine amino-transferase) in the blood is a known indicator for sarcopenia and frailty, however, no previous studies addressed the association of low ALT amongst patients hospitalized due to COPD exacerbation and long-term survival. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(28 reference statements)
2
19
0
2
Order By: Relevance
“…Serum ALT is a readily available, inexpensive, and routine biochemical assay used in clinical practice. A large number of studies have established the association between low ALT levels and sarcopenia and frailty in both middle-aged [ 22 ] and elderly patients [ 16 , 37 ] and in a myriad of clinical contexts [ 18 , 19 ]. A prospective study of 179 patients in an internal ward found that low ALT blood activity and high Frail questionnaire score correlated with increased mortality and with each other [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum ALT is a readily available, inexpensive, and routine biochemical assay used in clinical practice. A large number of studies have established the association between low ALT levels and sarcopenia and frailty in both middle-aged [ 22 ] and elderly patients [ 16 , 37 ] and in a myriad of clinical contexts [ 18 , 19 ]. A prospective study of 179 patients in an internal ward found that low ALT blood activity and high Frail questionnaire score correlated with increased mortality and with each other [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when the liver parenchyma is intact, ALT blood levels (demonstrated as catalytic activity) are a good marker for the whole-body skeletal muscle mass [ 14 , 15 ]. Utilizing the aforementioned, a large body of evidence accumulated in the past years, marking lower ALT values as a reliable marker for sarcopenia and frailty, in large, heterogeneous patient populations [ 16 , 17 , 18 , 19 ]. Characterizing sarcopenia and frailty status in patients with HF may provide clinicians with an indicator for gauging disease severity, prognosis, and disease progression or reversal.…”
Section: Introductionmentioning
confidence: 99%
“…(13,16) It was recently shown that low ALT levels are associated with reduced muscle strength, adverse outcomes in the general population of hospitalized patients, patients with chronic obstructive pulmonary disease exacerbation, and rehabilitation program participants. (12,15,16,32) To the best of our knowledge, this is the rst study to assess the correlation between low ALT and extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…A low ALT level in the peripheral blood is associated with low muscle mass. (12) Previous studies have demonstrated a correlation between ALT values and muscle mass, as assessed by CT measurements. (13) Recent studies in different clinical elds have shown that low ALT is a reliable biomarker for sarcopenia.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation